Track-density imaging of the human brainstem for anatomic localization of fiber tracts and nerve nuclei in vivo: initial experience with 3-T magnetic resonance imaging - Wenz, Holger; Al-Zghloul, Mansour; Kurth, Stefan; Groden, Christoph; Förster, Alex (World neurosurgery, 2016)
Background: The brainstem comprises a large variety of fiber tracts and nerve nuclei and is unarguably one of the most crucial parts of the brain. Reliable noninvasive visualization of its anatomy may help relate normal and pathological anatomic variations to neurologic/psychiatric disorders. In this study, we explored the potential of direction-encoded track-density imaging (TDI) for depicting the intricate anatomy of the brainstem. Methods: A total of 18 healthy volunteers (10 females, 8 males; median age, 34.5 years; interquartile range, 31-44.5 years) were examined on a 3-T MRI system. Diffusion tensor imaging data were processed using MRtrix to generate TDI images. These images were then compared with anatomic atlases to identify nerve nuclei and fiber tracts. The ability of TDI to delineate anatomic structures in the mesencephalon, pons, and medulla oblongata was evaluated using a 6-point Likert scale (5, excellent; 4, good; 3, moderate; 2, poor; 1, no adequate differentiation; 0, evaluation not possible). Results: All generated TDI images were evaluable without limitations. In the mesencephalon, delineation of the substantia nigra, crus cerebri, and red nucleus was rated as excellent, that of the medial lemniscus was rated as good, and that of the inferior colliculus was rated as poor. Delineation of all anatomic structures in the pons was rated as excellent. In the medulla oblongata, delineation of the pyramid was rated as excellent and that of the medial lemniscus as moderate, whereas delineation of the inferior olive was not possible. Conclusions: TDI images provide optimal delineation of nerve nuclei and fibers in the upper brainstem, but have more difficulty identifying more caudal structures.